The UK Hydrogen Strategy: Falling Behind in the Green Race? - Weko, Silvia (2023)
The UK aims to become a leader in green industries by developing a competitive hydrogen industry, bringing new jobs, and revitalizing peripheral areas of the country. Hydrogen is also seen as an opportunity for the country to improve its energy security, as extracting fossil fuels is increasingly costly and unfeasible given the UK’s decarbonization goals. Its hydrogen strategy takes a “twin track” approach, that is, simultaneously promoting hydrogen from gas with carbon capture and hydrogen from low-carbon electricity. The UK strategy focuses on the importance of applying hydrogen to industry including chemicals, steel, and glass. However, its funding and research initiatives rather place an emphasis on developing local hydrogen markets by using hydrogen for heating and transportation. In the short term, the UK aims to develop “blue” hydrogen, which is perceived as cheaper, to replace household gas use. Funding for hydrogen innovation comes from the government, but revenue support is likely to be funded by levies on energy consumption. This approach seems unlikely to result in the green industrial leadership the government hopes to achieve. The unwillingness of the government to take strategic decisions on hydrogen types and uses means that its funding is stretched across different cases. And, while the UK participates in international standard-setting initiatives to better participate in global markets, it is not officially coordinating with or investing in hydrogen infrastructure that could connect it with Europe and thereby enable regional hydrogen trade. Given the rise in industrial policy measures including for hydrogen in the US and EU, the UK’s goal of becoming a major hydrogen player seems unlikely without a significant change in policy clarity and ambitio